Elementary School Learners' Linguistic and Learning Awareness - Bagarić Medve, Vesna (Array, 2012)
This paper reports on an investigation of linguistic and learning awareness of 11-12- year- old elementary school learners of English, German, French and Italian as foreign languages in Croatia. The study was carried out as part of the large-scale project on implementing ELP as a means of promoting their learning autonomy. The 94 learners were prompted to prepare and perform short guided dialogues in pairs or small groups. While watching their videotaped oral presentations, learners were guided to reflect on their language performance through group discussion and individually by means of a questionnaire. The results of quantitative and qualitative analyses indicate that despite great individual differences, elementary school learners are aware of some phonetic, lexical and grammatical aspects of language and even more of the strategies that can enhance their learning process.